Adjunctive Use of Point of Care Ultrasound to Diagnose Compartment Syndrome of the Thigh - Neil Long; Justin S. Ahn; Daniel J. Kim (CINQUILL Medical Publishers Inc., 2021)
Compartment syndrome is a medical emergency and must be considered in patients who present with severe limb pain. Compartment syndrome is a clinical diagnosis, classically described as presenting with the 5 'P's (pain, pulselessness, pallor, paraesthesia, and paralysis). Apart from pain, the other findings signify acute arterial obstruction and would be late findings. We present a case of a 31-year-old male in which point of care ultrasound (POCUS) expedited this diagnosis by demonstrating a large thigh hematoma in the anterior compartment. This prompted emergent orthopedic surgery consultation, and the diagnosis of compartment syndrome was confirmed both at the bedside and in the operating room. Compartment syndrome can be a challenging diagnosis, especially early in the course of illness. While POCUS should not be used in isolation in the assessment of possible compartment syndrome, it can be used as an adjunct in the workup, especially if it identifies an underlying cause.